“Silence, brand”: Aftermath of language style overconvergence in digital marketing - Tan, Derrick Lin Kang (2024)
This research focuses on investigating language overconvergence and its effects on the perception of target audiences on the promoted brands and products in the field of digital marketing. The study proposes the communication accommodation theory (CAT) as a framework to analyse the instances of failure involving the inappropriate adaptation of language styles for targeted audiences which caused significant public backlash. The research aims to identify the underlying factors of language overconvergence in digital marketing, and its defining characteristics. The study is significant as it could help marketers avoid overconvergence by identifying the characteristics and factors that contribute to it, and ultimately create better marketing strategies and avoid potential failure and backlash, resulting in the damaged reputation of the marketing organization. The study conducted a quantitative study, surveying Malaysian Gen Z online users by presenting them case studies of overconvergence in digital marketing, and calculating the results through simple formulas to gauge the effects. Findings could help future studies to look into deeper detail to what extent these effects may manifest for different speech communities and languages.